PENGARUH MOTIVASI, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERATING PADA DINAS PARIWISTA DAN EKONOMI KREATIF PROVINSI RIAU - Jaya, Ujang; Marnis, Marnis; Harlen, Harlen (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to determine the influence of Motivation, organizationalculture and work environment on Performance at the Department of Tourism andCreative Economy of Riau Province. And to know Motivation, organizationalculture and work environment to Performance employees with job satisfaction asa moderating variable on the Department of Tourism and Creative Economy ofRiau Province.In this study set sample of 147 employees of civil servant status. Becausethe population is relatively large, then in this study sampling using slovin methodso that the respondents obtained as many as 60 respondents. Furthermore, dataanalysis using Moderated Regression Analysis (MRA) through software SPSS17.0 msi.The results showed that the influence of motivation, organizational cultureand work environment simultaneously on the performance of employees of theDepartment of Tourism and Creative Economy of Riau Province there is asignificant influence. The results showed that the motivation, organizationalculture and work environment simultaneously on performance with jobsatisfaction as moderating variables on the Department of Tourism and CreativeEconomy of Riau Province there is no significant influence.